Analytic Hierarchy Process in an Inspection Evaluation of National Parks’ Websites: The Case Study of Greece - KABASSI, Katerina; MARTINIS, Aristotelis; PAPADATOU, Athena (Journal of Environmental Management and Tourism; Vol 10 No 5 (2019): JEMT Volume X Issue 5(37) Fall 2019, 2019)
Internet and websites, thanks to their popularity, are powerful tools than can be used to inform local society and the visitors on the role of the Protected Areas and National Parks, their ecological value, the restrictions for visitors, the ecotourism activities and contribute to informing and raising awareness. In order to evaluate and compare the websites of National Parks, an inspection evaluation experiment is presented. As a case study we have used the websites of National Parks in Greece, as Greece has rich biodiversity and a lot of tourists visiting the country during the summer. In order to process the results of the evaluation, we used a Multi Criteria Decision Making Theory, namely Analytic Hierarchy Process (AHP). AHP has a formal way of quantifying the qualitative criteria of the alternatives and in this way removes the subjectivity of the results. The paper provides the basic steps of the experiment based on the advantages of the inspection methods and the steps of the AHP theory. The implementation of the particular experiment leads to conclusions about the electronic presence of National Parks in Greece.